Contextualization of the trajectory of the management report in the period from 2000 to 2014 from the point of view of Organizational Memory (OM) - Beux, Claudia Freire (Seven Editora, 2023)
This article is subject to contextualize the trajectory of the Management Report (RG) of the Federal University of Rio Grande do Sul (UFRGS) between the years 2000-2014, from the point of view of the Organizational Memory (OM), addressing the significant changes presents in the document and the management changes that it provided during this period.  The RG provides a part of the organizational history within a time slot. The information contained herein is following the documentary records that support the work and management decisions that underpin and are inserted from a legal perspective that it has submitted. The research, exploratory and qualitative it obtained through the website of the University and the sites of the Comptroller General of the Union (CGU) and the Court of Audit (CGU). We collected the data and annual information in the document, beginning with the year 2000 when the record was available for inspection.  Subsequently, these data were evaluated and compared to the requested content by the demands governing the preparation of the Management Report, stemming from the CGU and TCU, Supervisory Boards, and Control in the Federal Government.  The trajectory of the document in the period analyzed from the focus of Organizational Memory. It is for the article to provide the reader with a theoretical and technical perspective. The results point to the importance of the Management Report, not only as a management document but above all, as a portrait of the Organization, such as the completion of service, to be available as Memory. DOI:https://doi.org/10.56238/devopinterscie-165